RAPID PROGRESSION OF CLAVICULAR SOLITARY PLASMACYTOMA TO MULTIPLE MYELOMA - Hantoro Gunawan; Paulus Budiono Notopuro (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Introduction: Solitary plasmacytoma is a monoclonal plasma cell malignancy restricted to one tumor. Fifty percents of cases can progress to multiple myeloma (MM). Median time to progression is 19 months. A case about plasmacytoma progressing rapidly to MM within 2 months from initial diagnosis is hereby described. Case: A 45-year-old male, attended the Surgery clinic with the chief complaint of progressive swelling on the left neck for two months. Physical examination revealed a fixed, solid, 8x8 cm mass on the left supraclavicular. FNAB showed plasmacytoma. Surgical biopsy and immunohistochemistry confirmed the diagnosis of plasmacytoma. Ki67 index was 80%. There was no abnormality in laboratory examination. Two months later he was admitted to the Internal ward with anemia and kidney disorder. Serum protein electrophoresis revealed M-spike. BMA showed plasma cell proliferation with 78% proportion, which confirmed the diagnosis of MM. Discussion: Solitary plasmacytoma can occur on any bone, mostly on axial bones. Solitary plasmacytoma on clavicle is very rare, with prevalence 0.45% of all primary bone tumors. Diagnosis of solitary plasmacytoma relies on tissue biopsy, laboratory, radiology and bone marrow aspiration. Progression of plasmacytoma to MM can be detected from CBC and clinical chemistry results. Serum protein electrophoresis and bone marrow aspiration results confirmed the diagnosis of MM. High proliferation index (Ki67>8%) and tumor size(>5cm) were the risk factors for rapid progression of plasmacytoma. Conclusion: Early detection of systemic symptoms is very important in the management of solitary plasmacytoma. Keywords: solitary plasmacytoma, multiple myeloma